PENGAWASAN KEIMIGRASIAN TERHADAP WARGA NEGARA ASING PEMEGANG APEC BUSINESS TRAVEL CARD (ABTC): ANTARA FASILITASI DAN KONTROL DALAM PERSPEKTIF PERMENIMIPAS NOMOR 4 TAHUN 2025 - Graciella Dumaria Siahaan, Josephine; Mirwanto, Tony; Yuka Utami, Devina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the normative tension between facilitation and immigration control in the regulation of the APEC Business Travel Card (ABTC), referred to as Kartu Perjalanan Pebisnis (KPP) APEC, under Minister of Immigration and Correctional Affairs Regulation Number 4 of 2025. Using a normative juridical method with statute and conceptual approaches, this study finds a significant normative imbalance: the regulation grants extensive privileges to foreign holders including visa-free entry, 60-day stay permits, dedicated counters, and permission for tourism, without proportional supervisory mechanisms or sanctions. The concurrent Regulation Number 2 of 2025 on Immigration Supervision does not specifically address KPP APEC holders, and its Article 33(2) explicitly excludes visit permit holders from sponsor-based supervision. This normative disintegration creates a legal vacuum potentially undermining immigration control as mandated by Article 66 of Law Number 6 of 2011. The study recommends normative reconstruction through specific supervisory clauses and proportional sanctions integrated into the KPP APEC regulation.